Acute Response of Circulating Vascular Regulating MicroRNAs during and after High-Intensity and High-Volume Cycling in Children - Kilian, Yvonne; Wehmeier, Udo F.; Wahl, Patrick; Mester, Joachim; Hilberg, Thomas; Sperlich, Billy (Frontiers in Physiology, 2016)
Aim: The aim of the present study was to analyze the response of vascular circulating microRNAs (miRNAs; miR-16, miR-21, miR-126) and the VEGF mRNA following an acute bout of HIIT and HVT in children. Methods: Twelve healthy competitive young male cyclists (14.4 ± 0.8 yrs; 57.9 ± 9.4 ml·min-1·kg-1 peak oxygen uptake) performed one session of high intensity 4x4 min intervals (HIIT) at 90-95% peak power output, each interval separated by 3 min of active recovery, and one high volume session (HVT) consisting of a constant load exercise for 90 min at 60% peak power output. Capillary blood from the earlobe was collected under resting conditions, during exercise (d1 = 20 min, d2 = 30 min, d3 = 60 min), and 0, 30, 60, 180 min after the exercise to determine miR-16, -21, -126 and VEGF mRNA. Results: HVT significantly increased miR-16 and miR-126 during and after the exercise compared to pre values, whereas HIIT showed no significant influence on the miRNAs compared to pre values. VEGF mRNA significantly increased during and after HIIT (d1, 30`, 60`, 180`) and HVT (d3, 0`, 60`). Conclusion: Results of the present investigation suggest a volume dependent exercise regulation of vascular regulating miRNAs (miR-16, miR-21, miR-126) in children. In line with previous data, our data show that acute exercise can alter circulating miRNAs profiles that might be used as novel biomarkers to monitor acute and chronic changes due to exercise in various tissues.